Large force actuator using an electro-adhesive gel super multi-disk. (2nd October 2022) - Koyanagi, Ken'ichi; Takata, Yudai; Kakinuma, Yasuhiro; Anzai, Hidenobu; Sakurai, Koji; Oshima, Toru
Abstract : Actuators with clutch mechanisms have advantages in safety, backdriveability, and controllability for human-coexistence robots. This paper presents a large force actuator using electro-adhesive gels, which are functional materials controlled by the magnitude of an electric field. The developed actuator can generate and continuously control a force over 560 N and resist with a small force when de-energized. The number of electro-adhesive gel disks is drastically increased to increase the generative force. This paper reports the structural plan for the new actuator and experiments to investigate its basic characteristics. Based on the experimental results, an actuator model is identified for the future design of its control system. This paper contributes to the development of a clutch-type linear actuator with a large generative force, maintaining safety and a high force-to-weight ratio. It also addresses the problem of high-voltage power supply costs for electro-rheological and electro-adhesive materials. GRAPHICAL ABSTRACT: UF0001